2021
DOI: 10.1186/s13229-021-00417-x
|View full text |Cite
|
Sign up to set email alerts
|

Mind the translational gap: using iPS cell models to bridge from genetic discoveries to perturbed pathways and therapeutic targets

Abstract: Autism spectrum disorder (ASD) comprises a group of neurodevelopmental disorders characterized by impaired social interactions as well as the presentation of restrictive and repetitive behaviors. ASD is highly heritable but genetically heterogenous with both common and rare genetic variants collaborating to predispose individuals to the disorder. In this review, we synthesize recent efforts to develop human induced pluripotent stem cell (iPSC)-derived models of ASD-related phenotypes. We firstly address concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 191 publications
(240 reference statements)
0
11
0
Order By: Relevance
“…This intensified need for basic and clinical research can be partially met by the generation and use of new tissue specific transgenic animal models [18]. Very recently, neural cells and cerebral organoids derived from iPS have been isolated from TSC patient specimens and these cellular models could reproduce some neurological defects seen in TSC [8,19,20]. However, there is still a need for brain-specific in vitro TSC models which could be easily handled and are affordable for most research labs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intensified need for basic and clinical research can be partially met by the generation and use of new tissue specific transgenic animal models [18]. Very recently, neural cells and cerebral organoids derived from iPS have been isolated from TSC patient specimens and these cellular models could reproduce some neurological defects seen in TSC [8,19,20]. However, there is still a need for brain-specific in vitro TSC models which could be easily handled and are affordable for most research labs.…”
Section: Discussionmentioning
confidence: 99%
“…Other mouse models have required additional genetic events, such as loss of PTEN, which does not occur in TSC patients [6]. In addition, genetically engineered human cortical spheroid models and neural cell model of TSC from embryonic stem cell (ES) or induced pluripotent stem cells (iPS) with loss/mutation of TSC1/TSC2 have been generated [7,8]. However, their similarity to human TSC and SEGA is uncertain, and engraftment of such cell lines in immunodeficient mice has not been achieved, which is a hallmark of a tumor cell line.…”
Section: Introductionmentioning
confidence: 99%
“…For more directed assays, target gene expression via fluorescence reporters or cell-surface markers can be combined with flow cytometry to isolate populations that deviate from wild-type controls. Electrophysiological-or calcium-signaling assays will be able to pinpoint functional consequences in mutant neurons or cardiomyocytes [174,175]. Combining functional assays with mRNA sequencing such as Patch-seq [176] will directly link functional readouts with gene expression.…”
Section: Screening Strategies For Identifying Phenotypes Caused By Shared Genetic Variantsmentioning
confidence: 99%
“…In patients with sporadic forms, iPSCs represent a valuable method to investigate disease mechanisms in vitro. So far, studies have found phenotypes connected to calcium signaling, electrophysiology, cell proliferation, and synaptic density ( Pintacuda et al, 2021 ). Of note, among the many genes studied, various groups have focused on mutations of SHANK3 and SHANK2, structural proteins located at the postsynaptic density ( Chen et al, 2020 ; Lutz et al, 2020 ).…”
Section: Neuronal Models For Disorders Of the Brainmentioning
confidence: 99%